Communicative Translation on Ibrahim Abdurrahman al-Any's Minhaj al Tifli al Muslim Book - Muhammad Syihabuddin Asyraf; Ahmad Hifni; Muhammad Zacky Mubarok (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2022)
This study aims to translate the book Minhȃj al-Ṭifli al-Muslim by Dr. Ibrahim Abdurrahman Al-'Any and explain his responsibilities by outlining the translation strategy from the Arabic Source Language into the Target Language Indonesian. The method used is qualitative-descriptive so that the results of this translation can be accounted for to the maximum. The application of the communicative method uses four strategies: prioritizing and ending, adding, removing, and replacing. This study concludes that this strategy is quite effective because it can address gaps and differences in language and cultural norms between SL and TL more precisely. In addition to describing the translation strategy, this study also wants to explain the accountability process for the communicative translation of the book Minhȃj al-Ṭifli al-Muslim by Dr. Ibrahim Abdurrahman Al-'Any.